Unilateral retinitis pigmentosa - Bhattarai, D; Paudel, N; Adhikari, P; Gnyawali, S; Joshi, S N (Nepalese Journal of Ophthalmology, 2015)
Objective: To report a rare case of unilateral retinitis pigmentosa and to present the clinical features, and ¿ndings of multifocal ERG and visual field of this case.Case: A 70-year-old-female diagnosed as Retinitis Pigmentosa in right eye 7 years back, presented with further gradual painless diminution of vision in the very eye and without any similar symptoms in left eye. On examination, the findings (including multifocal ERG and visual field) suggested the features of retinitis pigmentosa in her right eye, while the other eye being unaffected.Conclusion: In this rare case, the distinct features of retinitis pigmentosa are seen only in one eye, and this can be further confirmed from multifocal ERG and visual field.